Regional and social disparities in cessation behavior and motivation to quit among U.S. adult current smokers, Tobacco Use Supplement to the U.S. Census Bureau's Current Population Survey 2014–15 and 2018–19 - Johnson, Candon; Martinez, Jose (Frontiers in Public Health, 2024)
Variation in cessation behaviors and motivators exist across the United States and potentially contribute to health disparities. This study examines regional differences over time in two cessation motivators (quit interest and doctor’s advice to quit smoking) and two cessation behaviors (past-year quit attempts and recent successful smoking cessation) by sex, age, race and ethnicity, education, marital status, employment status, and household income. Estimates come from two releases of the Tobacco Use Supplement to the U.S. Census Bureau’s Current Population Survey (TUS-CPS), 2014-15 and 2018-19. Using data from the 2018-19 TUS-CPS, prevalence of quit interest was highest in the Northeast and lowest in the Midwest; prevalence of doctor’s quit advice was highest in the Northeast and lowest in the West; prevalence of making a quit attempt in the past year was highest in the Northeast and lowest in the South; and prevalence of recent successful smoking cessation (defined as quit for 6 to 12 months) was highest, and nearly identical, in the Northeast and Midwest and lowest in the South. Compared to the 2014-15 survey, 14 demographics (7 in the Midwest; 6 in the South; and 1 in the West) observed decreases in quitting interest and taking actions to quit. While the Asian, non-Hispanic group in the Northeast had the largest decrease in quit interest ( 17.9%), this same group also observed an increase in recent successful smoking cessation (+369.2%). Reported quit interest over 2018-19 was generally highest among demographics in the Western region, those with the lowest prevalence of quit attempts and successful quitting were typically located within the South. Stark differences in quit interest and recent successful cessation were also found to exist between the oldest and youngest age groups. Our study fills a gap in the literature by providing estimates of cessation-related behaviors among demographics within regions and how these behaviors have changed across time. This study also highlights the need for additional research examining cessation behavior at more granular levels to help inform policies that may further reduce the overall health burden associated with smoking, including health disparities experienced by populations facing the highest barriers to cessation.